Pontine Infarct as Initial Presentation of Catastrophic Antiphospholipid Syndrome in Systemic Lupus Erythematous - Rathika Rajah; Rizna A Cader (Acta Medica Indonesiana)
Antiphospholipid syndrome (APLS) is an autoimmune condition which commonly manifests as an arterial or venous thrombosis affecting medium to large vessels, with the presence of antiphospholipid antibodies. APLS can be a primary disease by itself, or secondary to other autoimmune diseases, such as Systemic Lupus Erythematosus (SLE). Catastrophic APLS is a rare but a fatal sequelae of APLS, affecting up to three or more organs, and progresses rapidly with a high mortality rate. We report a case of catastrophic APLS in a young woman with underlying SLE who presented to us with multiple cranial nerve palsies due to bilateral pontine infarct, and eventually developed deep vein thrombosis and pulmonary embolism during the course of the illness. She was treated with high dose corticosteroids and intravenous cyclophosphamide with biochemical improvement. In this case report, we would like to highlight the fact that our patient had bilateral pontine infarcts as the initial presentation, with no inciting events and  antiphospholipid antibodies were negative during the acute illness.